The Relationship Between Physical Environmental Factors in the Home and the Incidence of Respiratory Infections in Children in Pasar Simundol Village - Indah Rahayu Ritonga; Yulia Khairina Ashar; Syafran Arrazy; Rapotan Hasibuan; Jufri Naldo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Acute respiratory infections (ARI) in toddlers remain an urgent health issue in Indonesia because toddlers are susceptible to infection due to their immature immune systems. The physical environment of the home plays a major role as a risk factor, especially in homes with poor ventilation, minimal lighting, high humidity, and inadequate sanitation. The objective of this study is to determine the relationship between housing density, the presence of ventilation, the presence of windows, lighting, and temperature with the incidence of ISPA in infants in Pasar Simundol Village. The research method used is quantitative with a cross-sectional design. The sample size in this study is 55 infants, calculated using the Lameshow formula. Data analysis was performed using univariate and bivariate analysis with the chi-square test. The results of the study showed a relationship between the presence of windows (PR = 1.697; p = 0.019 < 0.05), the presence of ventilation (PR = 1.080; p = 0.030 < 0.05), lighting (PR = 1.753; 0.011 < 0.05), temperature (PR = 1.733; p = 0.012 < 0.05), and humidity (PR = 1.853; p = 0.026), while there was no association with housing density (PR = 1.175; p = 0.832 > 0.05). It is recommended that the community improve the physical conditions of their homes, such as adding ventilation, windows, and maintaining cleanliness and lighting to reduce the risk of respiratory infections in infants.